Reduced graphene oxide doped tellurium nanotubes for high performance supercapacitor - Rani, Pinki; Alegaonkar, Ashwini P.; Biswas, Rathindranath; Jewariya, Yogesh; Kanta Haldar, Krishna; Alegaonkar, Prashant S. (Frontiers in Chemistry, 2022)
Supercapacitors have been achieving great interest in energy storage systems for the past couple of decades. Devices with superior performance, mainly, depending on the material architecture of the electrodes. We report on the preparation of Tellurium nanotubes (Te-tubes diameter ~100 nm and length ~ 700 nm), with variable doping of conducting of reduced graphene oxide (rGO) network to fabricate high-performance electrode characteristics of rGO @ Te. The prepared material was characterized using X-ray diffractometry, Fourier transforms infrared, Raman spectroscopy, and Field emission scanning electron microscopy, including Brunauer-Emmett-Teller, Barrett-Joyner-Halenda measurements. FTIR study revealed that 15% rGO @ Te has a wide C-O vibration band ~ 1100-1300 cm-1, however, another composition has a shallow C-O vibration band. The FESEM study shows the nanotube dispersion in rGO layers. In addition, the EDX study revealed that only 15 % of composition has an optimistic concentration of C and O element and in other composition either at lower/ higher rGO concentration an uneven count of C and O are observed. The electrochemical performance of rGO@ Te is found to be superior at 15 % composition over others thereby achieving specific capacitance Csp 170+ F/g @ 10 mV/s in a symmetric arrangement. The reported values are thirty times higher than pristine Te-tubes (5 F/g). This finding suggests that rGO @ Te is a promising candidate for supercapacitor.